Fabrication of high-flux SAPO-34 membrane on α-Al2O3 four-channel hollow fibers for CO2 capture from CH4. (March 2017) - Chen, Yang; Zhang, Yuting; Zhang, Chun; Jiang, Ji; Gu, Xuehong
Highlights: SAPO-34 membranes were synthesized on α-Al2 O3 multi-channel hollow fibers. Nano-size ball-milled seeds were used to induce membranes at a mild temperature. The membranes exhibited high permeation flux for CO2 /CH4 separation. Abstract: High-performance SAPO-34 membranes were synthesized on α-Al2 O3 four-channel hollow fibers (4CHF) for CO2 capture. Original and nano-size ball-milled seeds were adopted to induce SAPO-34 membranes. The effects of synthesis temperature and synthesis time were investigated. A uniform seed layer could be readily formed on external surface of the support by dip-coating with ball-milled seeds. The ball-milled seeds could accelerate the growth of SAPO-34 membrane due to small particle size and surface lattice defects. With induction of ball-milled seeds, high-quality zeolite membrane could be reproducibly prepared with reduced synthesis time. The separation performances of 4CHF supported SAPO-34 membranes were evaluated for separation of CO2 /CH4 binary mixture. High separation performance with a CO2 /CH4 separation selectivity of 160 and CO2 permeance of 1.18 × 10 −6 mol m −2 s −1 Pa −1 was achieved on a membrane induced with ball-milled seeds at 453 K for 18 h.